Design And Development Of A Differential Relay Prototype Using SCR For Single-Phase Transformers - Hendri Parulian Simatupang; Moranain Mungkin (CERED Indonesia Institute, 2025)
transformer, focusing on signal processing by the ADC module. The methods used include hardware design, simulation using MULTISIM, and experiments to determine the optimal parameters of the shunt resistor (R shunt) and capacitor to improve the relay response. The results show that the use of a current transformer (CT) with a ratio of 1000: 1 produces a secondary current that is too small (2.6mA - 7.7mA) to trigger the relay directly. By connecting two CTs in series and reversing the phase of one of them, the resulting voltage increases so that it is sufficient to activate the ADC module. The addition of R shunt (10K potentiometer) allows the secondary voltage to approach zero under normal conditions, while the use of a 4.7µF / 16V polar capacitor optimizes the performance of differential relay protection without sacrificing the indicator display function.